Advances and strategies for capillary electrophoresis in the characterization of traditional Chinese medicine: A review of the past decade (2011–2021) - Shamsi, Shahab A.; Patel, Jalpaben (Frontiers in Analytical Science, 2023)
Traditional Chinese Medicines (TCM) provide a valuable source for drug discovery and form a potential basis for drug development, but they also carry substantial safety risks due to adverse drug reactions and a lack of understanding of their mechanism of action. However, valid analytical methodologies for analyzing TCMs must be developed and promoted due to their highly complex composition. An extensive pursuit of published research and review of scientific papers implies increased efficiency and sensitivity of capillary electrophoresis (CE) have attracted many researchers. This review provides an in-depth assessment of CE applications for TCM analysis published in the open literature in the last decade (2011 to 2021). Our survey unveils that capillary zone electrophoresis (CZE) with ultraviolet (UV) detection is the frequently utilized capillary electromigration technique for the efficient separation, identification, and quantitation of various active components in highly complex matrices. The extraction methods, modifiers to the background electrolyte, pre-concentration techniques, and mass spectrometry (MS) detectors are employed to enhance CE's separation selectivity and sensitivity of TCM.